Are oxidative stress mechanisms the common denominator in the progression from hepatic steatosis towards non-alcoholic steatohepatitis (NASH)? - Tariq, Z; Green, C; Hodson, L (2014)
Non-alcoholic fatty liver disease (NAFLD) is not a single disease entity, rather it describes a spectrum of liver conditions that range from fatty liver (steatosis) to more severe steatosis coupled with marked inflammation and fibrosis [non-alcoholic steatohepatitis (NASH)] to severe liver disease such as cirrhosis and possibly hepatocellular carcinoma. Obesity, notably abdominal obesity, is a common risk factor for NAFLD. The pathogenesis from steatosis to NASH is poorly understood, and the 'two hit' model, as suggested nearly two decades ago, provides a feasible starting point for characterization of underlying mechanisms. This review will examine the oxidative stress factors ('triggers') which have been implicated as a 'second hit' in the development of primary NASH. It would be reasonable to assume that multiple, rather than single, pro-oxidative intracellular and extracellular triggers act in conjunction promoting oxidative stress that drives the development of NASH. It is likely that the common denominator of these pro-oxidative triggers is mitochondrial dysfunction. Understanding the contribution of each of these 'triggers' is an essential step in starting to understand and elucidate the mechanisms responsible for progression from steatosis to NASH, thus enabling the development of therapeutic targeting to prevent NASH development and progression.